Mechanisms of L-citrulline on phosphodiesterase 5 in erectile dysfunction intervention - Abdulhakeem Olarewaju Sulyman; Olawale Moshood Aliyu; Emmanuel Oladipo Ajani; Yusuf Folohunsho Abdulkareem; Isaac Ade Afe; Fathia Oluwakemi Abdulyakeen; Halimat Yusuf Lukman; Saheed Sabiu; Karishma Singh; Kuben Naidoo (Scientific African)
Erectile dysfunction (ED) is a prevalent condition linked to diabetes and cardiovascular diseases, with conventional treatments often associated with adverse effects. Plant-derived products, though less explored, offer potential alternatives. This study evaluated the inhibitory effect of citrulline from Citrullus lanatus on PDE5 activity using experimental and computational methods to explore its therapeutic potential. Citrulline is a precursor to arginine, a substrate for nitric oxide (NO) synthesis, which enhances vasodilation and blood flow. Its therapeutic potential in erectile dysfunction lies in its ability to boost NO production, improving penile blood flow and erection quality. Citrulline was extracted from Citrullus lanatus using an adsorbent-based method, and its inhibitory effect on PDE5 was assessed through enzymatic and kinetic analyses. Molecular docking and dynamics simulations were used to evaluate citrulline's binding interaction and stability with PDE5, validated by the RMSD value obtained following superimposition of citrulline with the native ligand of PDE5 and post-dynamic analyses. Citrulline exhibited a concentration-dependent inhibition of PDE5, with an IC50 value of 366.7 µM. Kinetic analyses further elucidated citrulline's non-competitive inhibition pattern while molecular dynamics analysis afforded assessment of the binding stability of citrulline with PDE5, both providing insights into its mechanism of action. Citrulline-PDE5 complex had a higher negative binding free energy (-45.06 ± 4.69 kcal/mol) relative to the conventional drug (sildenafil) (-13.86±10.23 kcal/mol). The citrulline-PDE5 also had lower root mean square fluctuations (1.11 ± 0.65) than sildenafil-PDE5 (1.25 ± 1.77). The findings suggest that citrulline effectively inhibits PDE5 in a non-competitive manner, with higher binding affinity and greater structural stability than sildenafil, highlighting its potential as a more stable and efficient PDE5 inhibitor. However, limitations include its relatively high IC50 and the need for in vivo validation, necessitating further studies to confirm its clinical viability in the development of potential drugs for the management of ED.